Correlation of the solid-state reactivities of racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate and its 4,4 `-bipyridine cocrystal with their crystal structures - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Structural Chemistry, 2014)
Racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate, C21H18O8, (1), shows a very efficient intermolecular benzoyl-group migration reaction in its crystals. However, the presence of 4,4 `-bipyridine molecules in its cocrystal, C21H18O8 center dot C10H8N2, (1)center dot BP, inhibits the intermolecular benzoyl-group transfer reaction. In (1), molecules are assembled around the crystallographic twofold screw axis (b axis) to form a helical self-assembly through conventional O-H center dot center dot center dot O hydrogen-bonding interactions. This helical association places the reactive C6-O-benzoyl group (electrophile, El) and the C4-hydroxy group (nucleophile, Nu) in proximity, with a preorganized El center dot center dot center dot Nu geometry favourable for the acyl transfer reaction. In the cocrystal (1)center dot BP, the dibenzoate and bipyridine molecules are arranged alternately through OH center dot center dot center dot N interactions. The presence of the bipyridine molecules perturbs the regular helical assembly of the dibenzoate molecules and thus restricts the solid-state reactivity. Hence, unlike the parent dibenzoate crystals, the cocrystals do not exhibit benzoyl-transfer reactions. This approach is useful for increasing the stability of small molecules in the crystalline state and could find application in the design of functional solids.
Keywords: acyl transfer; cocrystal; crystal structure; design of functional solids; helical assembly; hydrogen bonding; myo-inositol; solid-state reactions

Crystal structures of the pyrazinamide-p-aminobenzoic acid (1/1) cocrystal and the transamidation reaction product 4-(pyrazine-2-carboxamido)-benzoic acid in the molten state - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2015)
The synthesis of pharmaceutical cocrystals is a strategy to enhance the performance of active pharmaceutical ingredients (APIs) without affecting their therapeutic efficiency. The 1: 1 pharmaceutical cocrystal of the antituberculosis drug pyrazinamide (PZA) and the cocrystal former p-aminobenzoic acid (p-ABA), C7H7NO2- C5H5N3O, (1), was synthesized successfully and characterized by relevant solid-state characterization methods. The cocrystal crystallizes in the monoclinic space group P21/n containing one molecule of each component. Both molecules associate via intermolecular O-H center dot center dot center dot O and NH center dot center dot center dot O hydrogen bonds [O center dot center dot center dot O = 2.6102 (15)angstrom and O-H center dot center dot center dot O = 168.3 (19)degrees; N center dot center dot center dot O = 2.9259 (18) angstrom and N-H center dot center dot center dot O = 167.7 (16)degrees] to generate a dimeric acidamide synthon. Neighbouring dimers are linked centrosymmetrically through N-H center dot center dot center dot O interactions [N center dot center dot center dot O = 3.1201 (18) angstrom and N-H center dot center dot center dot O = 136.9 (14)degrees] to form a tetrameric assembly supplemented by C-H center dot center dot center dot N interactions [C center dot center dot center dot N = 3.5277 (19) angstrom and C-H center dot center dot center dot N = 147 degrees]. Linking of these tetrameric assemblies through N-H center dot center dot center dot O [N center dot center dot center dot O = 3.3026 (19) angstrom and N-H center dot center dot center dot O = 143.1 (17)degrees], NH center dot center dot center dot N [N center dot center dot center dot N = 3.221 (2) angstrom and N-H center dot center dot center dot N = 177.9 (17)degrees] and C-H center dot center dot center dot O [C center dot center dot center dot O = 3.5354 (18) angstrom and C-H center dot center dot center dot O = 152 degrees] interactions creates the twodimensional packing. Recrystallization of the cocrystals from the molten state revealed the formation of 4-(pyrazine-2-carboxamido) benzoic acid, C12H9N3O3, (2), through a transamidation reaction between PZA and p-ABA. Carboxamide (2) crystallizes in the triclinic space group P1 with one molecule in the asymmetric unit. Molecules of (2) form a centrosymmetric dimeric homosynthon through an acid-acid O-H center dot center dot center dot O hydrogen bond [O center dot center dot center dot O = 2.666 (3) angstrom and O-H center dot center dot center dot O = 178 (4) degrees]. Neighbouring assemblies are connected centrosymmetrically via a C-H center dot center dot center dot N interaction [C center dot center dot center dot N = 3.365 (3) angstrom and C-H center dot center dot center dot N = 142 degrees] engaging the pyrazine groups to generate a linear chain. Adjacent chains are connected loosely via C-H center dot center dot center dot O interactions [C center dot center dot center dot O = 3.212 (3) angstrom and CH center dot center dot center dot O = 149 degrees] to generate a two-dimensional sheet structure. Closely associated two-dimensional sheets in both compounds are stacked via aromatic pi-stacking interactions engaging the pyrazine and benzene rings to create a threedimensional multi-stack structure.
Keywords: acid-amide hetero-synthon; active pharmaceutical ingredient (API); cocrystal; crystal structure; hydrogen bonding; molten-state reaction; powder diffraction; transamidation reaction